The ectopic expression of myelin basic protein isoforms in Shiverer oligodendrocytes: implications for myelinogenesis (The Rockefeller University Press, 1991)
The myelin basic proteins (MBPs) are a set of peripheral membrane polypeptides that are required for the compaction of the major dense line of central nervous system myelin. We have used primary cultures of oligodendrocytes from MBP-deficient shiverer mice as host cells for the expression by cDNA transfection of each of the four major MBP isoforms. The distributions of the encoded polypeptides were studied by immunofluorescence and confocal microscopy and compared with patterns of MBP expression in normal mouse oligodendrocytes in situ and in culture. The exon II-containing 21.5- or 17-kD MBPs were distributed diffusely in the cytoplasm and in the nucleus of the transfectants, closely resembling the patterns obtained in myelinating oligodendrocytes in 9-d-old normal mouse brains. By contrast, the distribution of the 14- and 18.5-kD MBPs in the transfectants was confined to the plasma membrane and mimicked the distribution of MBP in cultures of normal adult oligodendrocytes. Our results strongly suggest that the exon II-containing MBPs are expressed first and exclusively during oligodendrocyte maturation, where they may play a role in the early phase of implementation of the myelination program. In contrast, the 14- and 18.5-kD MBPs that possess strong affinity for the plasma membrane are likely to be the principle inducers of myelin compaction at the major dense line.